Konseling Islami dengan Teknik Modelling untuk Mengatasi Emosi Negatif Anak Broken Home - Jannah, Miftahul; Nurjannah, Nurjannah (Universitas Mathla'ul Anwar Banten, 2022)
ISLAMIC COUNSELING WITH MODELING TECHNIQUES TO OVERCOME NEGATIVE EMOTIONS OF BROKEN HOME CHILDREN. This study intends to assist MZ clients in overcoming the problems they face, namely a broken home so that it affects the psychological condition of the child's personality, namely negative emotions. The counseling service used is Islamic counseling with modeling techniques. Negative emotions are shown in the form of being angry when being advised and reprimanded, slamming things, saying dirty words, and hurting yourself. This study uses a qualitative method. Data collection techniques were carried out by observation, interviews and home visits. The counseling process consists of several stages, namely: the initial stage, the activity stage and the final stage. After following a series of counseling processes, the results showed that there was a gradual change in the client's self from the habit of negative behavior now gradually decreasing and becoming positive behavior and being able to control his emotions well, this was the hope of his parents.